The Relationship Between Social Class and Generalized Trust: The Mediating Role of Sense of Control - Qiang, Ruichao; Li, Xiang; Han, Qin (Frontiers in Psychology, 2021)
The success and well-being theory of trust holds that higher social class is associated with higher generalized trust, and this association has been well documented in empirical research. However, few studies have examined the processes that might explain this link. This study extends this assumption to explore the mediating mechanism in the association. We hypothesized that social class would positively predict generalized trust, and the relationship would be mediated by people’s sense of control. Self-report data were collected from 480 adults (160 males, 320 females; ages 18–61) who participated through an online crowdsourcing platform in China. The results of multiple regression and mediation analyses supported the hypothesized model. This research provides further support for the success and well-being theory of trust, and builds on it by identifying greater sense of control as a possible explanation for the link between high social class and generalized trust. Limitations and possible future research are discussed.